2021
DOI: 10.7150/thno.54113
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as a novel therapeutic target for cardiovascular disease

Abstract: Cell death is an important component of the pathophysiology of cardiovascular disease. An understanding of how cardiomyocytes die, and why regeneration of cells in the heart is limited, is a critical area of study. Ferroptosis is a form of regulated cell death that is characterized by iron overload, leading to accumulation of lethal levels of lipid hydroperoxides. The metabolism of iron, lipids, amino acids and glutathione tightly controls the initiation and execution of ferroptosis. Emerging evidence shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
218
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(222 citation statements)
references
References 65 publications
3
218
0
1
Order By: Relevance
“…Previous studies have proven that ferroptosis plays an essential role in the occurrence and progression of various pathological processes and diseases, including intracerebral haemorrhage, 9 ischaemic stroke, 70 sepsis, 71 cancer, 72 and myocardial infarction. 73 More recently, several studies have indicated that ferroptosis is a potential therapeutic target for various lung diseases, such as acute lung injury, chronic obstructive pulmonary disease, pulmonary fibrosis, pulmonary infection and asthma ( Table 1 ). In this review, we summarize the association between ferroptosis and diverse lung diseases.…”
Section: Ferroptosis and Lung Diseasesmentioning
confidence: 99%
“…Previous studies have proven that ferroptosis plays an essential role in the occurrence and progression of various pathological processes and diseases, including intracerebral haemorrhage, 9 ischaemic stroke, 70 sepsis, 71 cancer, 72 and myocardial infarction. 73 More recently, several studies have indicated that ferroptosis is a potential therapeutic target for various lung diseases, such as acute lung injury, chronic obstructive pulmonary disease, pulmonary fibrosis, pulmonary infection and asthma ( Table 1 ). In this review, we summarize the association between ferroptosis and diverse lung diseases.…”
Section: Ferroptosis and Lung Diseasesmentioning
confidence: 99%
“…reducing the accumulation of ROS and thus the occurrence of ferroptosis. It has been reported that ferroptosis can be initiated both by direct inhibition of GPX4, and an essential intracellular antioxidant, GSH, which are the crucial proteins in glutaminolysis (Wu et al, 2021). When ferroptosis was first defined, it was induced by erastin which inhibited cystine uptake by the cystine/glutamate antiporter, leading to suppressed antioxidant defenses due to GSH reduction (Dixon et al, 2012).…”
Section: Abnormal Glutaminolysismentioning
confidence: 99%
“…Recently, several studies have indicated that ferroptosis contributes to the stress-induced deaths of cardiac and vascular cells ( Gao et al, 2015 ; Fang et al, 2019 ; Wang and Tang, 2019 ). It has been pointed out that targeting ferroptosis can serve as a feasible approach for preventing cardiomyocyte death and managing cardiac pathologies ( Ravingerová et al, 2020 ; Wu et al, 2021 ). In this review, we will describe the mechanism of ferroptosis and discuss the role of ferroptosis in the treatment of CVDs, thereby providing a novel therapeutic strategy for CVDs in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence proves that ferroptosis plays an important role in the development of many diseases (7,8), such as cancer, neurodegenerative diseases, ischemia/reperfusion injury, acute kidney injury, atherosclerosis, chronic obstructive pulmonary disease, and immune system diseases. Therefore, as an evolutionary program offers various druggable nodes, ferroptosis is supposed to be an emerging way to cure many kinds of diseases (9)(10)(11)(12)(13)(14). Especially as a therapeutic model in cancer treatment and prevention of ischemic organ damage, ferroptosis has been convincingly established (15).…”
Section: Introductionmentioning
confidence: 99%